DAMPAK DESENTRALISASI FISKAL TERHADAP PEMBANGUNAN DAERAH DI PROVINSI LAMPUNG - Erista Agustina; Eni Duwita Sigalingging (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The aim of this research is to identify imbalances in budget distribution and development between regions in Lampung Province, examine the obstacles faced by regional governments in implementing fiscal decentralization policies, and (provide recommendations for increasing the effectiveness of fiscal decentralization. The method used is that this research method uses a mixed approach (mixed methods), with data sources from journals, books, articles and other relevant sources. Then, the data collected was analyzed qualitatively and quantitatively. The results of this research were that there was an imbalance in budget distribution and development, in which regions have developed to receive larger budget allocations than underdeveloped regions. The main obstacles in implementing fiscal decentralization include limited human resource capacity, complicated bureaucratic procedures, and low community participation in budget planning and monitoring. Recommendations for overcoming these obstacles include increasing resource capacity. human resources, simplification of bureaucratic procedures, and increased community participation. In conclusion, the imbalance in budget distribution and obstacles in implementing fiscal decentralization affect the effectiveness of regional development in Lampung Province. Increasing local government capacity and community participation are needed to overcome this problem and increase the success of fiscal decentralization.